Analysis Of The Effect Of Good Corporate Governance, Company Profitability And Risk On Tax Avoidance - Wiandini Sranti Palupi; Nurul Hidayah; Tri Septyanto (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2020)
Taxes are one of the main sources of state revenue. The difference in interests between tax authorities and companies based on agency theory will lead to non-compliance by taxpayers or company management which has an impact on companies to do tax avoidance. Tax avoidance actions taken by companies can cause tax revenue by the state to be not optimal. This study aims to analyze the factors that influence tax avoidance. The variables used are GCG, Profitability, and Company Risk to assess the extent to which these variables affect tax avoidance. Based on the purposive sampling method with the period 2017 to 2019, a total of 54 samples from 18 companies were obtained. Hypothesis testing is carried out using multiple linear regression analysis. The results showed that the indicators of corporate risk variables had a positive effect on tax avoidance; the audit committee variable has a negative effect on tax avoidance; Independent commissioner variable, institutional ownership and profitability have no effect on tax avoidance